The effect of reducing administrative corruption is one of the indicators of administrative development in improving the performance of the health sector (Field study in public hospitals on the Syrian coast): The effect of reducing administrative corruption is one of the indicators of administrative development in improving the performance of the health sector (Field study in public hospitals on the Syrian coast) (Journal of Hama University, 2025)
The study aimed to determine the effect of reducing administrative corruption, one of the indicators of administrative development, along its dimensions (organizational corruption, behavioral corruption, financial corruption, and criminal corruption) in improving the performance of the health sector.The researcher relied on the deductive approach and relied on the descriptive approach to describe the research variables and analyze them based on the primary data collected. The researcher conducted a field study on public hospitals on the Syrian coast to collect the necessary primary data. The variables were also measured on all the primary data collected from During a questionnaire that was designed through the researcher’s review of previous studies and literature, and in order to test the hypotheses, the researcher transcribed the raw data into a database that was analyzed using SPSS version //20.The study found that the correlation coefficient between reducing administrative corruption and improving the performance of the health sector was 0.673, and this indicates that there is a link between reducing administrative corruption and improving the performance of the health sector, and this is what the hypotheses confirmed. The results of the study indicate that reducing administrative corruption is one of the indicators of development. Administration is very important for the hospital; Reducing administrative corruption plays a major role in improving the performance of the health sector, and the results of testing the four sub-hypotheses proved that there is a statistically significant relationship between the dimensions of reducing administrative corruption (reducing organizational corruption, reducing behavioral corruption, reducing financial corruption, reducing corruption Criminal) and the performance of the health sector, where the Pearson correlation coefficient reached respectively (0.646, 0.666, 0.757, 0.695), which indicates an acceptable and direct correlation between the dimensions of reducing administrative corruption and improving the performance of the health sector in the hospitals under study..
Keywords: Keywords: Administrative corruption; Administrative development; Organizational corruption, behavioral corruption, financial corruption, criminal corruption, health sector performance.